A Note from the Field in Search of Roland Wayne, Jr. (Not His Real Name): Comment on Social Connectivity - J Johnson Ralph (Journal of Public Health International, 2021)
This brief report article is a retrospective, descriptive, first-person account of following-up on a difficult-to-find client of an HIV/AIDS community-based pre-post intervention and disease prevention Research and Demonstration project in Houston, TX. Through the story about the personal journey of searching for the client, the author experiences an epiphany, especially in light of current events. Specifically, as opposed to social distancing and disconnection, public health disease prevention probably would be better served through leveraging the powerful and positive natural human features of social connectivity and closeness.
Keywords: Social Connectivity